Intelligent Reflecting Surface-UAV Systems in the Internet of Things Network: A Survey - Alsarayreh S.A.; Radzi N.A.M.; Alkahtani A.A.; Azmi K.H.M. (Institute of Electrical and Electronics Engineers Inc., 2024)
Intelligent reflecting surfaces (IRSs) and unmanned aerial vehicles (UAVs) are used in Internet of Things (IoT) networks to reduce costs, maximize energy efficiency, and provide a large coverage area through a flexible base station. IRS can reduce the power consumption in the UAV's system, as well as increase the line-of-sight probability. This paper highlights the importance of the IRS in improving the UAV system's performance. It also discusses the UAV components, how they work with the IRS hardware, and their working principles when they are separated or integrated. Then, we discuss several IoT system models using IRS and UAV to enhance the system's performance by maximizing energy efficiency, the achievable rate, and the signal received by the user equipment at ground level. Finally, the IRS-UAV system's open issues are explored, which include some system model scenarios, 3D-IRS-UAV systems, and new proposed solutions. This paper is the first study summarizing the types of IRS-UAV in cellular networks and the main open problems with new proposed solutions. This paper is important for researchers to understand the open issues in various IRS-UAV system scenarios and to develop their own IRS-UAV systems for various 5G network applications. 2013 IEEE.